Introducing Queer Studies in the Classroom: A Reflection - Hendri Yulius Wijaya (Jurnal Perempuan, 2016)
As a relatively new field of study, queer studies is still underexamined in Indonesian gender and sexuality discourse and studies. In addition to its complexities, examining and teaching sexualities in university is often perceived as ‘taboo’ and ‘indecent’. This claim becomes an impedement for queer studies to expand its coverage in tertiary institutions. In order to mainstream queer studies to public and university students, as a guest lecturer in several universities in Indonesia, the author tried to invent a participatory approach which put greater emphasis on reflexivity experience of the students, while the lecturer becomes a facilitator to generate meaningful and active discussions with the students. This reflection paper is an attempt to summarize the strategy of teaching queer studies in tertiary institutions, based on the author’s own teaching experience.